TEKNIK UJI LUARAN MODEL IKLIM AREA TERBATAS BERBASIS ANALISIS WAKTU-FREKUENSI WAVELET - Hidayat, Rahmat
Abstract : The result of output technique of limited area climate model based on wavelet time-frequency analysis is discussed in this thesis. So many evaluations have been done on model performance to simulate present climate, based on the direct comparison with the observation result. From the result of test done in 8 rainfall observation stations spread out in Indonesia, it is obtained the result that generally in most of the stations it is dominated by Annual Oscillation (AO), then 5 year Oscillation and Semi Annual Oscillation (SAO). However, in some station it is also detected 2 year Oscillation which is thought as phenomenon of Quasi Biennial Oscillation (QBO). There has not got the satisfying result yet, because the devation in some station where the devation is still large between observation result and output model. It is mostly determined by geographical site, topography, other local factor influences and model performance such as ocean dynamics component which has not been well represented in the model.